2415. Oral Vancomycin for Secondary Prophylaxis of Clostridium difficile Infections among High-risk Patients - Lew, Alison (Open Forum Infect Dis, 2019)
BACKGROUND: Clostridium difficile infection (CDI) is associated with high rates of recurrence, and major risk factors for recurrence include prior CDI episode(s) and antibiotic exposure. Prior studies concluded a reduction in CDI recurrence using oral vancomycin for prophylaxis (ppx), but were limited by prescriber bias and inclusion of all hospitalized adult patients with prior CDI and receipt of systemic antibiotics. We sought to determine whether or not oral vancomycin prophylaxis reduced CDI recurrence in high-risk patients. METHODS: This retrospective cohort study included patients > 2 years of age who had at least 2 episodes of CDI within the last year prior to broad-spectrum antibiotic exposure. The ppx cohort included patients who received oral vancomycin for > 50% of the duration of broad-spectrum antibiotic therapy, and the no ppx cohort included patients who received no oral vancomycin while on broad-spectrum antibiotics. Cohorts were compared via a univariate analysis. A Kaplan–Meier analysis was used to evaluate the time-to-event for development of CDI. RESULTS: Of 108 patients who met inclusion criteria, 88 patients were included in the no ppx cohort and 20 patients in the ppx cohort. The primary outcome of CDI incidence was numerically lower in the ppx cohort [13 (14.8%) vs. 2 (10%), p = 0.733]. Secondary outcomes within 12 weeks of broad-spectrum antibiotic initiation were similar between cohorts. The mean time from broad-spectrum antibiotic initiation to CDI recurrence was longer among the ppx cohort, suggesting a delay in time to CDI recurrence (29 + 25.9 vs. 57.5 + 26.1 days, p = 0.171). This delay led to a lower incidence of hospital acquired (HA) CDI in the ppx cohort [4 (30.8%) vs. 0 (0%), P > 0.99]. The Kaplan–Meier analysis (Figure 1) demonstrated no significant difference in time-to-event of CDI, p = 0.70. CONCLUSION: The use of oral vancomycin for secondary ppx of CDI was not shown to have a statistically significant difference in CDI recurrence compared with no ppx in this study. However, this may be due to the low sample size in the ppx cohort and low CDI event rates. The trend toward a delay in CDI recurrence and reduction in HA-CDI with the use of oral vancomycin is hypothesis generating. Further controlled studies are warranted to confirm the role of oral vancomycin for secondary ppx of CDI. [Image: see text] DISCLOSURES: All authors: No reported disclosures.